Penggunaan Media Digital dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam - Rizqi Amalia (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the role of digital media in enhancing students' learning motivation in Islamic Religious Education and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach using a library research method. Data were collected from books, scientific journals, research articles, and other relevant academic sources related to digital media and learning motivation. Data analysis was conducted through data reduction, data presentation, and descriptive conclusion drawing. The findings indicate that digital media positively influences students' learning motivation by providing attractive, interactive, flexible, and accessible learning experiences. Various digital learning tools, including educational videos, Learning Management Systems (LMS), e-books, educational applications, and online learning platforms, help students better understand Islamic Religious Education materials. Nevertheless, several challenges remain, such as limited technological infrastructure, unequal internet access, varying levels of teachers' digital competence, and the potential misuse of technology by students.